2007
DOI: 10.1161/circulationaha.107.724880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ranolazine, an Antianginal Agent With Novel Electrophysiological Properties, on the Incidence of Arrhythmias in Patients With Non–ST-Segment–Elevation Acute Coronary Syndrome

Abstract: Background-Ranolazine, a piperazine derivative, reduces ischemia via inhibition of the late phase of the inward sodium current (late I Na ) during cardiac repolarization, with a consequent reduction in intracellular sodium and calcium overload. Increased intracellular calcium leads to both mechanical dysfunction and electric instability. Ranolazine reduces proarrhythmic substrate and triggers such as early afterdepolarization in experimental models. However, the potential antiarrhythmic actions of ranolazine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
125
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(137 citation statements)
references
References 21 publications
6
125
0
6
Order By: Relevance
“…A total of 14 studies,8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 which reported data about the impact of ranolazine in ventricular arrhythmias, included in our systematic review (Figure 1). Of these, 2 were randomized controlled trials (MERLIN‐TIMI 36 and RAID), 1 was a randomized crossover trial (RYPPLE), 2 were observational studies, 1 was a case series, and 8 were case reports (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 studies,8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 which reported data about the impact of ranolazine in ventricular arrhythmias, included in our systematic review (Figure 1). Of these, 2 were randomized controlled trials (MERLIN‐TIMI 36 and RAID), 1 was a randomized crossover trial (RYPPLE), 2 were observational studies, 1 was a case series, and 8 were case reports (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…According to MERLIN‐TIMI 36 trial,10 ranolazine suppresses ventricular arrhythmias during the first week after admission for non‐ST elevation acute coronary syndrome, which can decrease the incidence of sudden cardiac death 22. Additionally, the RAID trial showed that ranolazine can significantly decrease VT episodes requiring antitachycardia pacing (ATP) compared to placebo patients while did not show a significant difference in the combined endpoint VT/VF or death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indirect decrease in intracellular Ca ++  concentration is responsible for the well‐documented antianginal effect of ranolazine 11, 12. In the field of clinical studies, ranolazine is presented as an effective, well‐tolerated, and safe drug, in patients with coronary artery disease and residual reversible ischemia 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence emphasizes the increase in VF threshold and the suppression of ischemia‐induced arrhythmias by ranolazine 17, 18. According to MERLIN‐TIMI 36 trial, ranolazine suppresses VA during the first week after admission for non‐ST elevation acute coronary syndrome 14. In such patients, even short VT episodes of only few beats are associated with the risk of sudden cardiac death 19.…”
Section: Discussionmentioning
confidence: 99%